(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Job satisfaction is a pleasurable or positive emotional state resulting from the appraisal of one’s job or job experience. Job satisfaction among teachers is very crucial to the long-term growth of any educational system around the world. However, many teachers in Kenya are leaving the teaching frontline for jobs in other sectors .For this reason, the study sought to find out the factors influencing job satisfaction among public secondary school teachers.